Management of Developmental Assessment In Improving The Quality of Learning for Students With Special Needs In Inclusive Schools - Indriani, Yulia; Wasliman, Iim; Hanafiah, Hanafiah; Ratnawulan, Teti (CV. Inara, 2022)
The present study reports the first comprehensive study on the freshwater macroinvertebrates and its habitat preferences in Bilah River, the largest riverin the Northern Sumatra. The riverside is characterized by the presence of anthropogenic and industrial activities which may alter the macroinvertebrate assemblage and biodiversity. Five months of investigation on 10 sampling stations from December 2016 to October 2017 was conducted based on the river flow in Bilah River. Principal component analysis indicated a decrease in trophic status from upstream to downstream of the river. A total of 27 taxa were recorded, with the most abundant group The developmental task of a child is something that appears at a certain period in the life span, if one phase fails it will cause various difficulties in completing the next phase of development. This is experienced by students with special needs (PDBK). Currently, the reality of teachers in the field is that they do not understand how to identify and assess these developmental phases for GDPK, which is a prerequisite for supporting success in the academic field. The purpose of this study was to find out how the implementation of developmental assessments in the two inclusive organizing schools, Ibnu Sina and Mutiara Bunda, in finding the actual GDPK profile through the “Daming Cycle” management theory approach from W. Edward Daming. In particular, this study describes and analyzes (1) plan, (2) Do, (3) Check and (4) action on developmental assessment using Sallis Edward's quality theory and Huvinggurst's developmental theory. This study uses a descriptive method with a qualitative approach. Collecting data by conducting observations, interviews, and study of documentation and validation of research results by conducting FGD (forum group discussion). The results of the study indicate that the management of developmental assessments at the inclusive schools of Ibnu Sina and Mutiara Bunda has been carried out by adjusting the existing concept rules, although in its implementation there are still obstacles, especially in terms of parental commitment and teacher understanding in GDPK confectionery.